Factors Related to the Incident of Early Marriage Among Adolescent Women in Mandailing Natal District Year 2022 - Nirma Juli Saputri; Fazidah A. Siregar; Heru Santosa (RIRAI Publisher, 2024)
Early marriages are marriages carried out by women under the age of 20 years. In North Sumatra, the most early marriages are in Mandailing Natal Regency at 22.70 percent, followed by North Labuhan Batu 21.73 percent and Deli Serdang and Langkat 20.27 percent. The participation of school age children who are not in school aged 16-18 years, Mandailing Natal is in fourth place in North Sumatra with a proportion of 27.3 percent, which is in line with the percentage of female reproductive couples aged under 19 years, where Mandailing Natal is 18 .95 percent due to the trend of early marriage due to school dropout (DO). The aim of this research is to analyze the factors that influence the incidence of early marriage in Mandailing Natal Regency in 2022. The design of this research is cross sectional with a sample size of 95 people consisting of 44 married early and 51 not married early. Data processing was carried out using univariate and bivariate analysis using the chi square test. Of the five significant variables found that influence the incidence of early marriage, namely level of knowledge (p=0.024), attitude (p=0.030), belief (p=0.036), parenting style (p=0.001), role of peers (p=0.028). It is hoped that there is a need to provide education to teenagers regarding the impact of early marriage on reproductive health and education to parents to provide an approach to children from an early age and provide an understanding of marriage, the problems that will arise when married and change the habit that states that those married after 20 years are considered spinsters.